Optimal random sampling for spectrum estimation in dasp applications - Tarczyński, Andrzej; Qu, Dongdong (Zielona Góra: Uniwersytet Zielonogórski)
In this paper we analyse a class of DASP (Digital Alias-free Signal Processing) methods for spectrum estimation of sampledsignals. These methods consist in sampling the processed signals at randomly selected time instants. We construct estimatorsof Fourier transforms of the analysed signals.
Keywords: digital alias-free signal processing; random sampling; spectral analysis; optimal sampling